Transcriptional regulation of the anthocyanin biosynthesis pathway in developing grapevine berries in cultivar ‘Malbec’ by putative R2R3 MYB negative regulators - Muñoz, Claudio Javier (2019)
In grapevine, proanthocyanins (PAs) and anthocyanins are obtained via the phenylpropanoid pathway. These metabolites are synthesized in specific tissues of the berry and accumulate in different developmental stages. The transcriptional control of the route is affected by transcription factors (TFs), mainly R2R3- Myb type, which can act as activators or repressors. Here we studied the fine regulation of the pathway by analysing the expression profiles of nine TFs operating as activators of the route as well as two main structural genes. In addition, we analysed the profiles of six R2R3-Myb subgroup 4 TFs described as repressors of the route (VviMybC2-L1, VviMybC2-L2, VviMybC2-L3, VviMyb4a, VviMyb4b and VviMyb4-like). The analysis of gene expression was carried out in five different development stages of the berry and in two berry tissues (skin and flesh) of cultivar ‘Malbec’. On the other hand, the putative R2R3-Myb repressors were analysed and compared in the tenturier cultivar ‘Alicante Bouschet’, in the same tissues and stages of development as ‘Malbec’. Concerning the R2R3-Myb repressors, our results indicate that in the ‘Malbec’ skins, VviMyb4a and VviMyb4b would act on the early genes of the route while VviMybC2-L2 and VviMyb4-like are co-expressed towards the end of the anthocyanin biosynthesis. In addition, the VviMybC2-L1 and VviMybC2-L3 are induced at two stages of development, first towards the end of the green phase of the berry, indicating the possible synergistic interaction by repressing the synthesis of PAs, then they are induced again towards maturation to inhibit the synthesis of anthocyanins. On the other hand, our results showed that the expression profiles of Myb repressor genes may explain the presence of colour in the flesh of Alicante Bouschet variety.